PENERAPAN SISTEM INFORMASI PENJUALAN DENGAN PLATFORM E-COMMERCE PADA PERUSAHAAN DAERAH APOTEK SARI HUSADA DEMAK - Arina Nur Syahputri; Dimas Aryo Anggoro (LPPM STMIK STIKOM Indonesia, 2020)
Sari Husada Pharmacy is one of the regional companies engaged in drug sales in Demak Regency. The company prioritizes innovation in information technology to face globalization and modern business competition in the industrial era 4.0. Improved services are needed so they can add regular customers and provide comfort to the existence of e-commerce. E-commerce solutions will overcome the problem of some customers who do not easily reach the location of the pharmacy because the transaction activities do not have to be in one place and it is difficult to check the stock of the drug, so that information systems are made more effective and efficient. The method used uses SDLC application development, namely waterfall. This method consists of five sequences, including: analysis, design, coding, testing, and implementation. This information system is created using PHP programming with CodeIgniter, Javascript, CSS (Bootstrap) and Sublime Text frameworks and database management using PHPMyAdmin which is installed together in Xampp, Apache Web Server and MySQL. The testing technique uses Blackbox and User Acceptance Test (UAT). The results of calculations from the User Acceptance Test (UAT) is 85,4% determine that the information system is very good to implemented at Sari Husada Pharmacy.